Nganjuk’s Inter-Religious Harmony Forum (FKUB) in Handling House of Worship Permit Disputes of Gereja Sidang Jemaah Allah (GSJA) in Kanakan, Nganjuk - Effendy, Gita Ajeng; Mahfud, Agus (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2021)
This study aims to find out the description of conflict resolution in the construction of houses of worship which is handled under the auspices of the FKUB (Fokum Kerukunan Umat Beragama). This research uses descriptive qualitative method by using purposive sampling. The theory used is Talcot Parson's perspective on the theory of action which is focused on the structural-functional. By this theory, it is connected to the theory of action that members of FKUB are trying to become volunteers who are able to solve problems by mutual consensus. Members of FKUB, in resolving also use several ways that do not violate the norms and rules that apply in the community. The existence of FKUB is able to provide answers that are sufficient for deliberation for the community.